2015
DOI: 10.1007/s40474-015-0064-4
|View full text |Cite
|
Sign up to set email alerts
|

“Shall We Play a Game?”: Improving Reading Through Action Video Games in Developmental Dyslexia

Abstract: Impaired linguistic-phonological processing is the most accepted explanation of developmental dyslexia (DD). However, growing literature shows that DD is the result of the combination of several neurocognitive causes. Visual attention and magnocellular-dorsal (MD) pathway deficits are now considered causes of DD. Interestingly, a large portion of literature showed that action video games (AVG) are able to improve attentional and perceptual skills in typical readers. Consequently, employing AVG trainings in ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 190 publications
(134 reference statements)
2
29
0
1
Order By: Relevance
“…Impairments in multisensory nonspatial attention are specifically associated with the disorder (criterion 2) and are found also in biological unaffected siblings (criterion 4; Table S5). These findings are consistent with the multisensory SAS hypothesis (Hari & Renvall 2001), according to which impairment in rapidly engaging attention represents a core deficit in DD and one of the most important predictors of reading (dis)abilities (Franceschini et al , 2013(Franceschini et al , 2015Gori et al, 2016a,b).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Impairments in multisensory nonspatial attention are specifically associated with the disorder (criterion 2) and are found also in biological unaffected siblings (criterion 4; Table S5). These findings are consistent with the multisensory SAS hypothesis (Hari & Renvall 2001), according to which impairment in rapidly engaging attention represents a core deficit in DD and one of the most important predictors of reading (dis)abilities (Franceschini et al , 2013(Franceschini et al , 2015Gori et al, 2016a,b).…”
Section: Discussionsupporting
confidence: 84%
“…These findings are consistent with the multisensory SAS hypothesis (Hari & Renvall ), according to which impairment in rapidly engaging attention represents a core deficit in DD and one of the most important predictors of reading (dis)abilities (Franceschini et al . , , ; Gori & Facoetti ; Gori et al ., ,b).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been shown that playing AVGs enhances a range of cognitive abilities including working memory (Gong et al, 2016), spatial cognition (Feng et al, 2007), response selection and execution (Hutchinson, Barrett, Nitka, & Raynes, 2016), object tracking (Green & Bavelier, 2012), visual selective attention (Chisholm & Kingstone, 2015;Green & Bavelier, 2003) and motion perception (Green, Pouget, & Bavelier, 2010b;Hutchinson & Stocks, 2013). In addition, training on AVGs improves reading abilities in children with developmental dyslexia (Franceschini et al, 2013;Franceschini et al, 2015;Gori, Seitz, Ronconi, Franceschini, & Facoetti, 2015) (see Karimpur & Hamburger (2015) for a review on the role of AVGs in psychological research). Hutchinson and Stocks (2013) found that action video game players have lower coherence threshold for radially moving patterns (e.g., contracting vs. expanding motion), but not for translational or rotational moving patterns presented in the fovea.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been shown that specific phonological awareness training does not always automatically transfer to better reading skills (e.g., Galuschka, Ise, Krick, & Schulte-Körne, 2014;but see Ball & Blachman, 1988;Bradley & Bryant, 1983;Moats, 1994, for positive effects of the phonological awareness training on reading remediation in children with DD). It is important to note that recent studies suggest that also other neurocognitive deficits might cause DD (Valdois, Bosse, & Tainturier, 2004; e.g., Boets, Vandermosten, Cornelissen, Wouters, &Ghesquière, 2011;Franceschini, Bertoni, Gianesini, Gori, & Facoetti, 2017;Franceschini, Gori, Ruffino, Pedrolli, & Facoetti, 2012;Franceschini, Trevisan et al, 2017;Franceschini et al, 2013Franceschini et al, , 2015Gori, Bertoni, et al, 2016;Gori, Molteni, & Facoetti, 2016;Gori, Seitz, , Franceschini, & Facoetti, 2016;Kevan & Pammer, 2009). Indeed, it can be assumed that DD is a multi-componential and probabilistic, rather than uni-causal and deterministic, neurodevelopmental disorder of learning to read (e.g., Carroll, Solity, & Shapiro, 2016;Franceschini et al, 2012).As a case in point, alongitudinalstudy by Clark and colleagues (2014) showed that the primary neuroanatomical abnormalities that precede DD are in lower-level areas responsible for visual and auditory processing, and frontal-attentional functions.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Visual attention deficit is now considered a cause of DD, independently from the auditory-phonological abilities (e.g., Franceschini et al, 2012Franceschini et al, , 2013Franceschini et al, , 2015Gabrieli & Norton, 2012;Gori, Seitz, et al, 2016). The visual-orthographic system receives attention orienting influence that modulates all visual processing levels (for reviews see Corbetta& Shulman, 2002Shulman, , 2011Facoetti, 2012;Vidyasagar & Pammer, 2010) from the primary visual cortex (V1) to the visual word form area.…”
Section: Research Evidencementioning
confidence: 99%